Pengaruh Penjualan Dan Beban Pajak Penghasilan Terhadap Laba Bersih Pada Perusahaan Sawit Di BEI - Bisma Wardana; Niken Ayuningrum; Pramesti Nurul Adinda (LP2M Politeknik Jambi, 2024)
This study aims to determine the extent of the effect of sales and income tax expenses on net income. The population of this study is palm oil companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2022 period. Based on the Purposive Sampling method, the number of research samples was 6 companies. The analysis carried out in this study is a classical assumption test, multiple linear regression test, R2 determination coefficient test, hypothesis test. The measuring instrument used for this analysis is the SPSS program. The results of this study are based on (t-test), sales have no effect on partial net profit with a sig value of 0.822 > 0.05, while income tax expense affects net profit partially with a sig value of 0.000 < 0.05. Simultaneously (test f), sales and income tax expenses affect net income with Fvalue calculated > Ftable which is 129.669 > 3.32